ChemInform Abstract: Preparation, Crystal Structure, Vibrational Spectra, and Thermal Behavior of Rb2H2P2O6·2H2O. Issue 17 (28th April 2014) - Gjikaj, Mimoza; Wu, Peng; Brockner, Wolfgang
Abstract Single crystals of Rb2H2P2O6·2H2O are obtained from an equimolar aqueous solution of H4P2O6 and Rb2CO3 at 4 °C.